A positive electrode composite slurry and a method for preparing the same
Patent Information
- Application Number
- CN202611032560.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-07-13
- Publication Date
- 2026-10-30
AI Technical Summary
[0005]本申请提供一种正极复合浆料及其制备方法,旨在解决正极浆料中添加有机酸浆料助剂存在易产气、浆料易返碱凝胶、电极界面稳定性差、极片力学性能弱的技术问题
[0021]本申请有益效果包括:本申请所述正极复合浆料具有较强的抗凝胶能力,且粘度稳定性好;由其制备的钠离子电池界面性能好、在充放电过程中不产气,循环性能优异。
Smart Images

Figure CN123017873A_ABST
Abstract
Description
Technical Field
[0001] This application belongs to the field of sodium-ion battery technology, specifically relating to a positive electrode composite slurry and its preparation method. Background Technology
[0002] Sodium-ion batteries, with their advantages of abundant resources, low cost, and excellent low-temperature performance, have significant application value in large-scale energy storage, low-speed power batteries, and backup power supplies. Layered oxide cathode materials, due to their high reversible capacity, good rate performance, and mature preparation process, are currently the sodium-ion cathode systems with the fastest industrialization progress, among which O3 and P2 types are the most widely used.
[0003] However, layered oxide cathodes require excessive sodium salt replenishment during high-temperature sintering, leading to unreacted sodium salt residues on the powder surface and in the pores. Simultaneously, the abundant active sites on the material surface readily adsorb water and carbon dioxide from the air, generating alkaline impurities such as NaOH, Na₂CO₃, and NaHCO₃, resulting in a high alkalinity on the powder surface. In the NMP slurry system, these alkaline impurities continuously disperse, causing the slurry pH to exceed 10, creating a strongly alkaline environment. This strongly alkaline slurry continuously disrupts the CF bonds of the PVDF binder, triggering binder defluorination and chain segment crosslinking, leading to problems such as slurry thickening, particle agglomeration, and gelation. This easily causes coating defects such as coating breaks, uneven surface density, and electrode powder shedding and delamination, severely impacting battery production yield and batch consistency.
[0004] Currently, the industry commonly uses organic acids such as oxalic acid, citric acid, and maleic acid as slurry additives to reduce the pH of the slurry and inhibit gelation through acid-base neutralization. However, these acidic additives have several inherent technical defects and cannot fundamentally solve the industry's pain points. For example, organic acids are prone to thermal decomposition during the electrode baking stage, generating gases such as CO and CO2, which leads to micropores inside the electrode and surface bulging, causing increased battery self-discharge, cycle gas generation failure, and reduced battery safety and lifespan. Acidic residues can corrode the surface crystal structure of the positive electrode, accelerate the dissolution of transition metals during charging and discharging, deteriorate the stability of the electrode interface, and cause low initial coulombic efficiency and rapid capacity decay during cycles. In addition, existing single-function additives cannot simultaneously address the rheological stability of the slurry, anti-gel ability, and electrode interface performance. Various conventional compound systems have limited functions and cannot fundamentally solve the two core problems of slurry processing performance and battery electrochemical performance at the same time. Summary of the Invention
[0005] This application provides a positive electrode composite slurry and its preparation method, aiming to solve the technical problems of easy gas generation, easy alkali return and gelation, poor electrode interface stability, and weak electrode mechanical properties caused by adding organic acid slurry additives to the positive electrode slurry.
[0006] The first aspect of this application provides a positive electrode composite slurry, comprising the following raw materials in parts by weight: 93-96 parts of positive electrode material, 1-4 parts of conductive agent, 1-4 parts of binder, 0.1-1 parts of composite additive, and 20-100 parts of solvent;
[0007] The composite additive comprises the following raw materials in parts by weight: 30-60 parts aminophosphonate, 30-60 parts dispersant, and 5-15 parts borate ester coupling agent.
[0008] According to some embodiments of the positive electrode composite slurry described in this application, the mass ratio of aminophosphonate to dispersant in the composite additive is 1:0.8-1.25.
[0009] According to some embodiments of the positive electrode composite slurry described in this application, the positive electrode material includes sodium-electric layered transition metal oxide; preferably, the sodium-electric layered transition metal oxide includes O3-type layered oxide or P2-type layered oxide.
[0010] According to some embodiments of the positive electrode composite slurry described in this application, the conductive agent includes one or more of conductive carbon black, carbon nanotubes, and graphene.
[0011] According to some embodiments of the positive electrode composite slurry described in this application, the binder includes polyvinylidene fluoride.
[0012] According to some embodiments of the positive electrode composite slurry described in this application, the solvent includes NMP.
[0013] According to some embodiments of the positive electrode composite slurry described in this application, the aminophosphonate includes one or more of sodium ethylenediaminetetramethylenephosphonate, aminotrimethylenephosphonic acid, hydroxyethylidene diphosphonic acid, and sodium diethylenetriaminepentamethylenephosphonate.
[0014] According to some embodiments of the positive electrode composite slurry described in this application, the dispersant includes polyvinylpyrrolidone (PVP).
[0015] According to some embodiments of the positive electrode composite slurry described in this application, the borate coupling agent includes one or more of the following: short-chain linear alkyl borate esters with fewer than 8 carbon atoms, cyclic chelated borate esters, and fluorinated short-chain borate esters.
[0016] According to some embodiments of the positive electrode composite slurry described in this application, the borate coupling agent includes one or more of triisopropyl borate, tributyl borate, propylene glycol cycloborate, ethylene glycol cycloborate, trifluoroethyl borate, and trifluoroisopropyl borate.
[0017] A second aspect of this application provides a method for preparing the positive electrode composite slurry described in the first aspect of this application, comprising the following steps: (1) Mix the binder, aminophosphonate, dispersant, conductive agent, positive electrode material and solvent to obtain a mixture; (2) Add borate ester coupling agent to the mixture and mix, so that the borate ester coupling agent is adsorbed on the surface of the positive electrode particles and pre-bonded to obtain the positive electrode composite slurry.
[0018] According to some embodiments of the preparation method of the positive electrode composite slurry described in this application, the mixture containing borate ester coupling agent is further subjected to degassing treatment; preferably, the degassing treatment includes stirring the mixture under a vacuum of -0.09 to -0.1 MPa for 30-60 min to remove bubbles.
[0019] According to some embodiments of the preparation method of the positive electrode composite slurry described in this application, in step (1), the mixing temperature is 20-45℃ and the time is 6-10h.
[0020] A third aspect of this application provides a sodium-ion battery, including the positive electrode composite slurry described in the first aspect of this application or the positive electrode composite slurry obtained by the preparation method described in the second aspect of this application.
[0021] The beneficial effects of this application include: the positive electrode composite slurry described in this application has strong anti-gelling ability and good viscosity stability; the sodium-ion battery prepared from it has good interface performance, does not generate gas during charging and discharging, and has excellent cycle performance. Attached Figure Description
[0022] Figure 1 The figure shows the viscosity of the positive electrode composite slurry described in Examples 1-7 and Comparative Examples 1-4 of this application as a function of time. Detailed Implementation
[0023] The embodiments of the present invention are described in detail below. These embodiments are exemplary and intended to explain the present invention, and should not be construed as limiting the present invention.
[0024] In this invention, the terms "one embodiment," "some embodiments," "example," "specific example," or "some examples," etc., refer to a specific feature, structure, material, or characteristic described in connection with that embodiment or example, which is included in at least one embodiment or example of the invention. In this specification, the illustrative expressions of the above terms do not necessarily refer to the same embodiment or example. Furthermore, the specific features, structures, materials, or characteristics described may be combined in any suitable manner in one or more embodiments or examples. Moreover, without contradiction, those skilled in the art can combine and integrate the different embodiments or examples described in this specification, as well as the features of different embodiments or examples.
[0025] This application provides a positive electrode composite slurry, comprising the following raw materials in parts by weight: 93-96 parts of positive electrode material, 1-4 parts of conductive agent, 1-4 parts of binder, 0.1-1 parts of composite additive, and 20-100 parts of solvent; The composite additive comprises the following raw materials in parts by weight: 30-60 parts aminophosphonate, 30-60 parts dispersant, and 5-15 parts borate ester coupling agent.
[0026] The positive electrode composite slurry described in this application has strong anti-gelling ability, excellent slurry stability, and the electrode sheet prepared from it has high peel strength.
[0027] In some embodiments of this application, the mass ratio of aminophosphonate to dispersant in the composite additive is 1:0.8-1.25; for example, 1:0.8, 1:1, 1:1.05, 1:1.25, etc.
[0028] In some embodiments of this application, the cathode material includes sodium-ion layered transition metal oxide; NaxMO2, where M represents transition metals such as nickel, cobalt, iron, and manganese.
[0029] In some embodiments of this application, the sodium-electric layered transition metal oxide includes O3-type layered oxide or P2-type layered oxide.
[0030] In some embodiments of this application, the conductive agent includes one or more of conductive carbon black, carbon nanotubes, and graphene.
[0031] In some embodiments of this application, the adhesive includes polyvinylidene fluoride.
[0032] In some embodiments of this application, the solvent includes NMP.
[0033] In some embodiments of this application, the aminophosphonate includes one or more of sodium ethylenediaminetetramethylenephosphonate, aminotrimethylenephosphonic acid, hydroxyethylidene diphosphonic acid, and sodium diethylenetriaminepentamethylenephosphonate. Aminophosphonates possess multidentate chelating functional groups, which, in a neutral system, can chelate sodium ions, carbonate ions, and hydroxide ions dissociated from sodium hydroxide and sodium carbonate remaining on the surface of layered oxides, converting them into stable chelates. Because aminophosphonates are nearly neutral and do not release hydrogen ions, they completely avoid problems such as reversible alkali return, high-temperature gas generation, and crystal corrosion caused by traditional organic acid-base neutralization. Simultaneously, aminophosphonates only act on residual sodium impurities on the material surface and cannot penetrate the positive electrode crystal lattice, thus not consuming active sodium ions participating in the electrochemical reaction and having no negative impact on the battery energy density.
[0034] In some embodiments of this application, the dispersant includes polyvinylpyrrolidone (PVP). PVP is an amphiphilic polymer compound with polar pyrrolidone groups adsorbed on the surface of the positive electrode particles and the alumina coating layer, while the nonpolar carbon chains extend into the NMP solvent. It effectively inhibits powder agglomeration and sedimentation through steric hindrance. Simultaneously, PVP can form weak complexes with trace amounts of free sodium ions, further enhancing the alkali control effect. Furthermore, PVP is only physically adsorbed on the particle surface and does not completely cover the hydroxyl active sites on the alumina surface, leaving sufficient conditions for the reaction of the borate ester.
[0035] In some embodiments of this application, the borate coupling agent includes one or more of the following: short-chain linear alkyl borate esters with fewer than 8 carbon atoms, cyclic chelated borate esters, and fluorinated short-chain borate esters.
[0036] The borate coupling agent includes one or more of triisopropyl borate, tributyl borate, propylene glycol cycloborate, ethylene glycol cycloborate, trifluoroethyl borate, and trifluoroisopropyl borate. The alumina layer coated with the main material has a large number of Al-OH hydroxyl groups distributed on its surface. The borate molecules undergo a dehydration condensation reaction with Al-OH, forming a continuous BO-Al passivation film in situ during the slurry drying stage. This film has an amorphous borate network structure, possessing excellent sodium ion conductivity, which can reduce the charge transfer resistance at the solid-liquid interface; simultaneously, it passivates highly active sites on the positive electrode surface, effectively suppressing the dissolution of transition metals such as Mn, Ni, and Fe during charge and discharge, reducing interfacial side reactions, and improving battery cycle stability. The formed BO-Al film has a uniform thickness and does not block ion transport channels, allowing for normal sodium ion conduction under both high and low rate conditions.
[0037] This application also provides a method for preparing the positive electrode composite slurry described in the first aspect of this application, comprising the following steps: (1) Mix the binder, aminophosphonate, dispersant, conductive agent, positive electrode material and solvent to obtain a mixture; (2) Add borate ester coupling agent to the mixture and mix, so that the borate ester coupling agent is adsorbed on the surface of the positive electrode particles and pre-bonded to obtain the positive electrode composite slurry.
[0038] In some embodiments of this application, the method further includes a step of degassing the mixture containing the borate coupling agent.
[0039] In some embodiments of this application, the degassing treatment includes stirring the mixture under a vacuum of -0.09 to -0.1 MPa for 30-60 minutes to remove air bubbles.
[0040] In some embodiments of this application, in step (1), the mixing temperature is 20-45°C and the time is 6-8h.
[0041] This application also provides a sodium-ion battery, comprising the positive electrode composite slurry described in the first aspect of this application or the positive electrode composite slurry obtained by the preparation method described in the second aspect of this application. The sodium-ion battery described in this application exhibits good interface performance, does not generate gas during charging and discharging, and demonstrates excellent cycle performance.
[0042] The technical solution of this application will be further described below with reference to specific embodiments.
[0043] Example 1 A method for preparing a positive electrode composite slurry includes the following steps: (1) Add 1000ml of anhydrous NMP to a stirred tank, add 60g of polyvinylidene fluoride (PVDF) powder in batches, and disperse at 4000rpm for 3h to obtain a uniform transparent solution. Control the temperature ≤45℃ during stirring. Add 4.5g of aminotrimethylenephosphonic acid and 3.6g of polyvinylpyrrolidone (PVP) to the solution, and stir at 30℃ and 4000rpm for 90min until the additives are completely dispersed. Then degas under -95kpa vacuum for 1h. Add 90g of conductive carbon black and 2841g of sodium-based layered oxide Na[Ni] to the reaction solution. 1 / 3 Fe 1 / 3 Mn 1 / 3 O2, stir and knead at 25℃ and 2000rpm for 1 hour to make the powder evenly dispersed; (2) Add 0.9g of tributyl borate to the reaction solution obtained in step (1), stir to make it uniformly adsorbed on the surface of the positive electrode particles and pre-bonded, add NMP to adjust the viscosity of the slurry, control the discharge viscosity at 5500±1000cps, and then stir for 45min under -95kPa vacuum to remove bubbles, and obtain the positive electrode composite slurry.
[0044] Example 2 The only difference between the preparation method of the positive electrode composite slurry in Example 2 and that in Example 1 is that the amount of aminotrimethylene phosphonic acid and polyvinylpyrrolidone added during the preparation of the positive electrode composite slurry in Example 2 is 3.6g and 4.5g, respectively.
[0045] Example 3 The only difference between the preparation method of the positive electrode composite slurry in Example 3 and that in Example 1 is that the amount of aminotrimethylene phosphonic acid and polyvinylpyrrolidone added during the preparation of the positive electrode composite slurry in Example 3 is 5.0 g and 3.1 g, respectively.
[0046] Example 4 The only difference between the preparation method of the positive electrode composite slurry in Example 4 and that in Example 1 is that the amount of aminotrimethylene phosphonic acid and polyvinylpyrrolidone added during the preparation of the positive electrode composite slurry in Example 4 is 3.1g and 5.0g, respectively.
[0047] Example 5 The only difference between the preparation method of the positive electrode composite slurry in Example 5 and that in Example 1 is that propylene glycol cycloborate is used instead of tributyl borate in the preparation process of the positive electrode composite slurry in Example 5.
[0048] Example 6 The only difference between the preparation method of the positive electrode composite slurry in Example 6 and that in Example 1 is that triisooctyl borate is used instead of tributyl borate in the preparation process of the positive electrode composite slurry in Example 6.
[0049] Example 7 The only difference between the preparation method of the positive electrode composite slurry in Example 7 and that in Example 1 is that trifluoroethyl borate is used instead of tributyl borate in the preparation process of the positive electrode composite slurry in Example 7.
[0050] Comparative Example 1 The only difference between the preparation method of the positive electrode composite slurry in Comparative Example 1 and Example 1 is that oxalic acid is used instead of composite additives in the preparation of the positive electrode composite slurry in Comparative Example 1.
[0051] The specific operating steps include: (1) Add 1000ml of anhydrous NMP to a stirred tank, add 60g of polyvinylidene fluoride (PVDF) powder in batches, and disperse at 4000rpm for 3h to obtain a uniform transparent solution. The temperature is controlled at ≤45℃ during stirring. Add 0.5g of oxalic acid to the solution and stir at 25℃ and 4000rpm for 90min until the additive is completely dispersed. Then degas under -95kpa vacuum for 1h. Add 90g of conductive carbon black and 2841g of sodium-based layered oxide Na[Ni] to the reaction solution. 1 / 3 Fe 1 / 3 Mn 1 / 3 O2 was stirred and kneaded at 25℃ and 2000rpm for 1 hour to ensure uniform dispersion of the powder. (2) Add NMP to adjust the viscosity of the slurry, control the discharge viscosity at 5500±1000cps, and then stir for 45 minutes under -95kPa vacuum to remove bubbles, and obtain the positive electrode composite slurry.
[0052] Comparative Example 2 The only difference between the preparation method of the positive electrode composite slurry in Comparative Example 2 and Example 1 is that oxalic acid and polyvinylpyrrolidone are used instead of composite additives in the preparation of the positive electrode composite slurry in Comparative Example 2, and the mass ratio of oxalic acid to polyvinylpyrrolidone is 4:1.
[0053] Comparative Example 3 The only difference between the preparation method of the positive electrode composite slurry in Comparative Example 3 and Example 1 is that no borate ester coupling agent is added during the preparation of the positive electrode composite slurry in Comparative Example 3.
[0054] Comparative Example 4 The only difference between the preparation method of the positive electrode composite slurry in Comparative Example 4 and Example 1 is that aminophosphonates are not added during the preparation of the positive electrode composite slurry in Comparative Example 4.
[0055] Performance Study of the Positive Electrode Composite Slurry Described in Examples 1-7 and Comparative Examples 1-4 of this Application Experimental method: The positive electrode composite slurry described in Examples 1-7 and Comparative Examples 1-4 of this application was coated onto aluminum foil, and then dried and rolled to obtain sodium ion positive electrode sheets (coating amount of 30 mg / cm² on both sides). 2 ).
[0056] The above-mentioned electrode sheets were selected to test the peel strength, and a 5Ah soft-pack battery was assembled to test the cycle performance of 1C charging and 1C discharging. The results are shown in Table 1.
[0057] The viscosity of the positive electrode composite slurry described in Examples 1-6 and Comparative Examples 1-4 of this application changes over time as follows: Figure 1 As shown.
[0058] Table 1 Comparison of electrode peeling performance and cycle performance after rolling.
[0059] From Table 1 and Figure 1 The results show that, compared with the comparative examples, the electrode slurries prepared in Examples 1-6 of this application have better slurry storage stability, electrode peel strength and battery cycle life. That is, the positive electrode composite slurry described in the examples of this application has better overall performance in terms of slurry processing characteristics, electrode mechanical properties and electrochemical cycle performance.
[0060] Comparing Examples 1-4, it can be seen that the stability, peel strength and cycle performance of the positive electrode composite slurry described in Examples 1-2 of this application are significantly better than those of the positive electrode composite slurry described in Examples 3-4. That is, the ratio of aminophosphonate to dispersant is the key influencing factor for regulating the above performance.
[0061] Comparing the test results of Examples 1-2 and Comparative Examples 3-4 of this application, it can be seen that the battery cycle performance prepared by the positive electrode composite slurry of Examples 1-2 of this application is significantly better than that of Comparative Examples 3-4. That is, there is a significant synergistic effect among the components of the positive electrode composite slurry of this application, and the absence of any one component will prevent the achievement of ideal cycle performance.
[0062] Comparing the test data of Example 1 with Examples 5-7 of this application, it can be seen that the battery cycle performance prepared using the positive electrode composite slurry of Examples 1, 4, and 5 is significantly better than that of Example 7. This indicates that the molecular structure of the borate ester coupling agent in the positive electrode composite additive of this application has a decisive influence on the final cycle performance of the battery, and not all borate ester coupling agents can achieve excellent cycle stability.
[0063] Although the above embodiments have been shown and described, it is understood that the above embodiments are exemplary and should not be construed as limiting the present invention. Any changes, modifications, substitutions and variations made to the above embodiments by those skilled in the art are within the protection scope of the present invention.
Claims
1. A positive electrode composite slurry, characterized in that, The raw materials include the following parts by weight: 93-96 parts of positive electrode material, 1-4 parts of conductive agent, 1-4 parts of binder, 0.1-1 parts of composite additive and 20-100 parts of solvent; The composite additive comprises the following raw materials in parts by weight: 30-60 parts aminophosphonate, 30-60 parts dispersant, and 5-15 parts borate ester coupling agent.
2. The positive electrode composite slurry according to claim 1, characterized in that, The mass ratio of aminophosphonate to dispersant in the composite additive is 1:0.8-1.
25.
3. The positive electrode composite slurry according to claim 1, characterized in that, The cathode material includes a sodium-electric layered transition metal oxide; Preferably, the sodium-electric layered transition metal oxide includes O3-type layered oxide or P2-type layered oxide.
4. The positive electrode composite slurry according to claim 1, characterized in that, The conductive agent includes one or more of conductive carbon black, carbon nanotubes, and graphene. And / or, the adhesive comprises polyvinylidene fluoride; And / or, the solvent includes NMP.
5. The positive electrode composite slurry according to claim 1, characterized in that, The aminophosphonate includes one or more of sodium ethylenediaminetetramethylenephosphonate, aminotrimethylenephosphonic acid, hydroxyethylidene diphosphonic acid, and sodium diethylenetriaminepentamethylenephosphonate; And / or, the dispersant includes polyvinylpyrrolidone.
6. The positive electrode composite slurry according to claim 1, characterized in that, The borate coupling agent includes one or more of the following: short-chain linear alkyl borate esters with fewer than 8 carbon atoms, cyclic chelated borate esters, and fluorinated short-chain borate esters. Preferably, the borate coupling agent includes one or more of triisopropyl borate, tributyl borate, propylene glycol cycloborate, ethylene glycol cycloborate, trifluoroethyl borate, and trifluoroisopropyl borate.
7. The method for preparing the positive electrode composite slurry according to any one of claims 1-6, characterized in that, Includes the following steps: (1) Mix the binder, aminophosphonate, dispersant, conductive agent, positive electrode material and solvent to obtain a mixture; (2) Add borate ester coupling agent to the mixture and mix, so that the borate ester coupling agent is adsorbed on the surface of the positive electrode particles and pre-bonded to obtain the positive electrode composite slurry.
8. The method for preparing the positive electrode composite slurry according to claim 7, characterized in that, It also includes a step of degassing the mixture containing borate ester coupling agent; Preferably, the degassing treatment includes stirring the mixture under a vacuum of -0.09 to -0.1 MPa for 30-60 minutes to remove air bubbles.
9. The method for preparing the positive electrode composite slurry according to claim 7, characterized in that, In step (1), the mixing temperature is 20-45℃ and the time is 6-10h.
10. A sodium-ion battery, characterized in that, Includes the positive electrode composite slurry according to any one of claims 1-6 or the positive electrode composite slurry obtained by the preparation method according to any one of claims 7-9.
